FACIAL ARTERY ON FACE - A STUDY ON SOUTH INDIAN CADAVERS AND SPECIMENS - Quadros, Lydia S.; Babu, Arathy; D'souza, Antony Sylvan (Journal of Health and Allied Sciences NU, 2013)
Context: Facial artery is usually the main artery supplying the face. It gives three named branches on the face, the inferior labial, the superior labial and the lateral nasal and continues as the angular artery. Face is also supplied by the transverse facial artery and the arteries accompanying the cutaneous nerves.Aim: In the present study, variations of facial artery on face were observed.Settings & design: Department of Anatomy, Kasturba Medical College, Manipal.Material & method: The present study was performed on 38 males and 12 females' formalin-fixed hemi-faces. Diameter of facial artery was noted at two specific points using a fine microcaliper.Results: The variations were divided into 3 categories. Out of 38 male hemi-faces, 100% right and 78% left hemi-faces belonged to type I category; 22% left hemi-faces belonged to Type III category. Out of 12 female hemi-faces, 80% right and 80% left hemi-faces belonged to Type I category, 18% left hemi-faces belonged to Type II category and 20% right and 2% left hemi-faces belonged to Type III category. Premasseteric branch was observed in 4 hemi-faces; a duplex with a prominent lateral angular branch was observed in 4 hemi-faces and anenlarged transverse facial artery was seen in 2 hemi-faces. The diameter of facial artery at its origin and at the antero-inferior angle of masseter muscle was larger in males.Conclusion: This study shows that the variations in the branches and the diameter of the facial artery were relatively larger in males when compared to females.
Keywords: Angular artery; facial artery; inferior labial artery; lateral nasal artery; premasseteric branch; superior labial artery